Earlier use of capsule endoscopy in inpatients with melena or severe iron deficiency anemia reduces need for colonoscopy and shortens hospital stay - Yung, Diana E.; Koulaouzidis, Anastasios; Douglas, Sarah; Plevris, John N. (Endoscopy International Open, 2018)
Background and study aims Capsule endoscopy(CE) is a well-established investigation for iron deficiency anemia (IDA) and melena, usually following negative upper and lower endoscopy. We aimed to study the effect of earlier CE in the investigative pathway for inpatients with IDA or melena at a large tertiary referral centre.Patients and methods We analyzed inpatients undergoing CE for IDA or melena from 2005 to 2017, without signs/symptoms suggesting lower gastrointestinal tract pathology. Patients underwent CE following negative upper and lower gastrointestinal endoscopy (Group 1), or negative upper gastrointestinal endoscopy (UGIE) only (Group 2).Results One hundred and seventy inpatients underwent CE for IDA (n = 44) and melena (n = 126). In Group 1, 46/95 (48.4%) patients had small bowel (SB) findings. CE found 16/95 (16.8 %) gastric and 12/95 (12.6 %) colon findings. Three of 12 patients with colon findings required repeat colonoscopy. One hundred and three colon investigations were carried out for 95 admissions. In Group 2, 33/75 (44.0%) patients had SB findings. There were 12/75 (16.0 %) gastric and 11/75 (14.7 %) colon findings. In patients with positive CE, significant colonic findings led to colonoscopy in 10 of 39 patients (diagnostic yield 6/10). Thirty-six patients had negative CE; 15 underwent colonoscopy (diagnostic yield 9/15). The remaining 21 of 36 patients with no further colonoscopy did not develop adverse outcomes related to colonic pathology. Twenty-six colon investigations were carried out in 75 admissions. Patients in Group 2 had shorter mean times from admission to CE (5.08 ± 3.80 vs. 6.38 ± 3.80 days; P = 0.02) and hospital stays (10.5 ± 9.58 vs. 12.5 ± 11.4 days; P = 0.04) compared to Group 1.Conclusion Earlier use of CE in inpatients with melena or IDA, no signs of lower gastrointestinal pathology and negative UGIE resulted in shortened hospital stays, significant DY from both small bowel and upper gastrointestinal tract, and two-thirds less unnecessary colon investigations without affecting clinical outcomes.